2011
DOI: 10.1097/jac.0b013e3181ff6ef2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Culture and Practice Systems in Primary Care

Abstract: The patient-centered medical home is an approach to comprehensive primary care relying on well-developed systems. Research has shown that for practices to meet patient-centered medical home requirements, care models may need to be redesigned. However, there is a dearth of information about what factors are important to achieve this goal. Self-report surveys from 293 staff across 42 practices in Minnesota showed variation in use of systems and dimensions of organizational culture. Organizational cultures that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Organizations should create infrastructures to promote NP-physician relations such as clear guidelines for NP and physician teamwork with the goal to provide best care to patients. The primary care settings with supportive organizational attributes such as collegiality are more likely to provide better patient care (Dugan, Mick, Scholle, Steidle, & Goldberg, 2011). Understanding the physician and NP relationship is crucial to understanding the organizational climate and improving primary care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations should create infrastructures to promote NP-physician relations such as clear guidelines for NP and physician teamwork with the goal to provide best care to patients. The primary care settings with supportive organizational attributes such as collegiality are more likely to provide better patient care (Dugan, Mick, Scholle, Steidle, & Goldberg, 2011). Understanding the physician and NP relationship is crucial to understanding the organizational climate and improving primary care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research also established that an organizational culture that emphasizes quality is related to the existence of practice improvement activities (Dugan et al. ). Our case study research supports this finding and provides additional evidence that leadership priorities and support greatly influenced practice improvement efforts.…”
Section: Discussion and Conceptual Frameworkmentioning
confidence: 99%
“…When considering the patients side there are studies showing that patient satisfaction and quality of care is the same or better if nurses take over certain tasks from physicians autonomously [28–30]. On the other hand, one recent U.S. study found that those organizational cultures that emphasized collegiality and quality but not autonomy were related to quality evaluation and improvement [31]. …”
Section: Discussionmentioning
confidence: 99%